Parental Religious Guidance Through Communication Patterns In Overcoming Self-Injury In Adolescents - Izah, Reza Izzatul; Bafadal, Iqbal; Fakhri, Mohammad; Fadhilah, Ninda Nurul; Zulfa, Milatul (Yayasan Alpatih Harapan Semesta, 2023)
Self-injury behavior is a form of behavior used to cope with emotions, problems, and emotional pain by hurting oneself without any direct intention of committing suicide. Other studies have found that adolescents have a high intention to engage in self-harming behavior due to various factors such as economic problems, family problems, lack of attention, or broken homes. The role of parents is very much needed in shaping the character of children and providing guidance, especially religious guidance. The method used in this study was a descriptive qualitative approach with subjects who were adolescents with self-injury behavior in Central Lombok Regency. Data analysis used data reduction, and data validation used source triangulation. The results of this study indicate that religious guidance and the application of effective communication patterns can reduce the potential for self-harm among adolescents. There was a decrease in self-harming behavior.